Sex chromosome complement determines sex differences in aromatase expression and influences aromatase regulation by gonadal hormones in developing neurons - Cambiasso, María Julia (2015)
Fil: Cambiasso, María Julia. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Biología Celular B; Argentina.